Effects of phenolic-rich extracts of Clinacanthus nutans on high fat and high cholesterol diet-induced insulin resistance - Nadarajan, Sarega; Imam, Mustapha Umar; Mohd Esa, Norhaizan; Zawawi, Norhasnida; Ismail, Maznah (BioMed Central, 2016)
Background: Clinacanthus nutans is used traditionally in many parts of Asia to improve well-being, but there are limited studies on its efficacy. We explored the potential use of C. nutans for prevention of high fat and high cholesterol diet-(HFHC-) induced insulin resistance in rats. Methods: The leaf of C. nutans was extracted using water (AL extract) and methanol (AML extract), and the extracts were fed to rats alongside the HFHC diet for 7 weeks, and compared with simvastatin. Oral glucose tolerance test, and serum insulin, retinol binding protein 4 (RBP4), adiponectin and leptin were measured. Homeostatic model assessment of insulin resistance (HOMA-IR) was computed, while transcriptional regulation of hepatic insulin signaling genes was also assessed. Results: Glycemic response was higher in the HFHC group compared with the AL and AML groups, which also had lower serum RBP4, fasting glucose, insulin and HOMA-IR. Serum adiponectin levels were higher, while leptin levels were lower in the AML and AL groups compared to the HFHC group. There was upregulation of the Insulin receptor substrate, phosphotidyl inositol-3-phosphate, adiponectin receptor and leptin recetor genes, in comparison with the HFHC group. Conclusions: Overall, the results showed that the HFHC diet worsened metabolic indices and induced insulin resistance partly through transcriptional regulation of the insulin signaling genes. C.nutans, on the other hand, attenuated the metabolic effects and transcriptional changes induced by the HFHC diet. The results suggested that C.nutans may be a good source of functional ingredient for the prevention of insulin resistance.